Mutant allele-specific CRISPR disruption in DYT1 dystonia fibroblasts restores cell function - Cruz, Lilian; Bence, György; Cheah, Pike See; Kleinstiver, Benjamin P.; Eimer, William A.; Garcia, Sara P.; Sharma, Nutan; Ozelius, Laurie J.; Cristopher, Bragg D.; Joung, Keith J.; Norberto de Souza, Osmar; Macedo Timmers, Luis Fernando Saraiva; et al. (Elsevier, 2020)
Most individuals affected with DYT1 dystonia have a heterozygous 3-bp deletion in the TOR1A gene (c.907_909delGAG). The mutation appears to act through a dominant-negative mechanism compromising normal torsinA function, and it is proposed that reducing mutant torsinA may normalize torsinA activity. In this study, we used an engineered Cas9 variant from Streptococcus pyogenes (SpCas9-VRQR) to target the mutation in the TOR1A gene in order to disrupt mutant torsinA in DYT1 patient fibroblasts. Selective targeting of the DYT1 allele was highly efficient with most common non-homologous end joining (NHEJ) edits, leading to a predicted premature stop codon with loss of the torsinA C terminus (delta 302–332 aa). Structural analysis predicted a functionally inactive status of this truncated torsinA due to the loss of residues associated with ATPase activity and binding to LULL1. Immunoblotting showed a reduction of the torsinA protein level in Cas9-edited DYT1 fibroblasts, and a functional assay using HSV infection indicated a phenotypic recovery toward that observed in control fibroblasts. These findings suggest that the selective disruption of the mutant TOR1A allele using CRISPR-Cas9 inactivates mutant torsinA, allowing the remaining wild-type torsinA to exert normal function.